Study on phase behavior and properties of binary blends of bio-oil/fossil-based refinery intermediates: A step toward bio-oil refinery integration. (1st June 2018) - Manara, P.; Bezergianni, S.; Pfisterer, U.
Highlights: Refinery compatible entry points to directly co-feed bio-based refinery intermediates. Binary blends of 30 wt% HDT-Bio-oil/fossil-based refinery intermediates were tested. Phase behavior and fuel properties of bio-oil/fossil-based refinery intermediates. FCC LCO and LVGO are promising candidates for co-processing with HDT-Bio-oil. Abstract: To defossilize the current liquid energy backbone a sustainable renewable substitute for fossil crude oil is required. The long–term aim is to increase the co-feed of renewables beyond the current level. However, technical constrains and certain properties limit the conventional biogenic co-feed level to less than 10%. The potential of identifying refinery compatible entry points to directly co-feed bio-based refinery intermediates and further co-process in existing petroleum crude oil refineries is investigated in the current study. The studied pyrolysis bio-oil has been upgraded via mild hydrotreatment (HDT) in order to fulfil specifications and become a "drop-in" biofuel in compatible refinery "location". The properties of HDT-Bio-oil as well as fossil-based refinery intermediates were compared and five fossil-based refinery intermediates have been concluded as potential candidates for co-processing. The miscibility of the aforementioned renewable and conventional fuels has been investigated. Among all refinery streams, Fluid Catalytic Cracking Light Cycle Oil (FCC LCO) and secondly Light Vacuum Gas Oil (LVGO) have been concluded to be the most promising candidates for co-processing, resembling HDT-Bio-oil's properties.